2006
DOI: 10.1094/phyto-96-1372
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Soil Suppressiveness Against Rhizoctonia solani by Incorporation of Dried Plant Residues into Soil

Abstract: Suppressive effects of soil amendment with residues of 12 cultivars of Brassica rapa on damping-off of sugar beet were evaluated in soils infested with Rhizoctonia solani. Residues of clover and peanut were tested as noncruciferous controls. The incidence of damping-off was significantly and consistently suppressed in the soils amended with residues of clover, peanut, and B. rapa subsp. rapifera 'Saori', but only the volatile substance produced from water-imbibed residue of cv. Saori exhibited a distinct inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
0
12
0
2
Order By: Relevance
“…For example, certain Brassica species release volatile compounds that have direct inhibitory effects on the growth of many pathogens (e.g. Gimsing and Kirkegaard 2006;Kasuya et al 2006;Mayton et al 1996). Other crops such as hairy vetch (Vicia villosa; Zhou and Everts 2004) as well as various oat species and varieties, have been found to suppress several soilborne pathogens including nematodes (Elmer and LaMondia 1999;Vilich 1993).…”
Section: Effects Of Diversity On Diseasesmentioning
confidence: 99%
“…For example, certain Brassica species release volatile compounds that have direct inhibitory effects on the growth of many pathogens (e.g. Gimsing and Kirkegaard 2006;Kasuya et al 2006;Mayton et al 1996). Other crops such as hairy vetch (Vicia villosa; Zhou and Everts 2004) as well as various oat species and varieties, have been found to suppress several soilborne pathogens including nematodes (Elmer and LaMondia 1999;Vilich 1993).…”
Section: Effects Of Diversity On Diseasesmentioning
confidence: 99%
“…This suggests that biological antagonism induced by residue amendment was impeded by low soil pH. It was previously shown that, while suppression of Rhizoctonia damping-off of sugar beet in a soil amended with dried residues of clover or Komatsuna was completely nullified by treating the soil with antibacterial antibiotics, disease suppressiveness in the peanut residue-amended soil declined only partially after the same soil treatment (Kasuya et al 2006). Considering that soil bacteria in general are less tolerant to low soil pH than soil fungi (Davet 2004), the results suggest that bacterial antagonists were associated with the disease suppression induced by Komatsuna residue.…”
Section: Discussionmentioning
confidence: 96%
“…by incubating the residue-amended soil for 3-4 weeks before sowing sugar beet seeds, even though Pythium damping-off was enhanced when the seeds were sown soon after residue amendment (Kasuya et al 2010). It is noteworthy that the peanut residue induced disease suppressiveness against R. solani when incorporated into fallow upland field soil as well as into paddy field soils with long-term applications of only organic or inorganic fertilizers (Kasuya et al 2006). This suggests that the precise roles of antagonists including those colonizing the phyllosphere of peanut deserve further investigation to fully understand the mechanism of disease suppression induced in the residue-amended soils.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations